2012
DOI: 10.1364/ol.37.001856
|View full text |Cite
|
Sign up to set email alerts
|

Z-scan measurement of the nonlinear refractive index of graphene

Abstract: Under strong laser illumination, few-layer graphene exhibits both a transmittance increase due to saturable absorption and a nonlinear phase shift. Here, we unambiguously distinguish these two nonlinear optical effects and identify both real and imaginary parts of the complex nonlinear refractive index of graphene. We show that graphene possesses a giant nonlinear refractive index n(2)≃10(-7) cm(2) W(-1), almost 9 orders of magnitude larger than bulk dielectrics. We find that the nonlinear refractive index dec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
399
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 613 publications
(428 citation statements)
references
References 16 publications
25
399
2
2
Order By: Relevance
“…At first, the transmission was 61% for the probe light, but it increased to 78% when the pump and probe pulses overlapped, which indicates that the transparency window has a blue-shift resulting from the negative nonlinear refractive index of the multilayer-graphene micro-sheet/ZnO nanoparticle layer and the monolayer graphene/polycrystalline ITO layer. 35,36 This is confirmed by the calculated transmission spectrum (Figure 4f) of the metasurface sample under the excitation of a 1.5 kW cm 22 pump laser. Thus, a tunable wavelength range of up to 120 nm was realized for MIT.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…At first, the transmission was 61% for the probe light, but it increased to 78% when the pump and probe pulses overlapped, which indicates that the transparency window has a blue-shift resulting from the negative nonlinear refractive index of the multilayer-graphene micro-sheet/ZnO nanoparticle layer and the monolayer graphene/polycrystalline ITO layer. 35,36 This is confirmed by the calculated transmission spectrum (Figure 4f) of the metasurface sample under the excitation of a 1.5 kW cm 22 pump laser. Thus, a tunable wavelength range of up to 120 nm was realized for MIT.…”
Section: Resultssupporting
confidence: 66%
“…The effective refractive index of the multilayer-graphene micro-sheet/ZnO nanoparticle layer and the monolayer graphene/polycrystalline ITO layer was decreased, resulting from the optical Kerr effect under the excitation of the pump laser. 35,36 Accordingly, the plasmonic modes provided by the gold nanoprism dimers have a blue-shift, and the transparency window has a blue-shift. To further verify the measured time delay, we calculated the transmission spectrum of the metasurface sample under different pump intensities.…”
Section: Resultsmentioning
confidence: 99%
“…Owing to its gapless, linear charge-carrier dispersion relation [3,4], graphene is capable of relatively strong, broadband coupling with light [5,6], and offers a large electrically-tunable optical response [7]. Valence and conduction electrons in this material present a uniform velocity that clearly emphasizes their anharmonic response to external fields, which has stimulated considerable interest in the graphene nonlinear optical properties [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Further motivation to study optical nonlinearities in monolayer graphene is provided by the availability of interband optical transitions within a continuous range of low photon energies, accompanied by a high electrical mobility [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…It has been indicated [12] that the nonlinear response of graphene is essentially dispersionless over the wavelength and much stronger compared to bulk semiconductors. It has been experimentally demonstrated that the nonlinear refractive index of graphene is as n 2 ≈ 10 ⁻7 cm 2 W ⁻1 [13] using the Z-scan technique. After that, optical bistability, self-induced regenerative oscillations, and four-wave mixing (FWM) have been consecutively observed in graphene-silicon hybrid optoelectronic devices [14].…”
Section: Introductionmentioning
confidence: 99%